2.4 GHz Energy Harvester for Ultra-Low Power IoT Sensor Applications - Vauzia, Farrah; Sulaeman, Enceng; Taryana, Yana (Jurnal Elektronika dan Telekomunikasi, 2025)
IoT is a technology that integrates various devices and can be controlled remotely via the internet. Currently, IoT is rapidly developing in sectors such as health, agriculture, housing, and more. Sensors play an essential role in IoT devices to collect information from the surrounding environment. The sensors rely on batteries as a power source, which affects their performance. Recent technologies have developed ultra-low power sensors to extend the battery life. However, using batteries for IoT devices over a long period is not cost-effective and efficient in terms of installation. To address this issue, an Energy Harvester system has been developed. This system collects energy from the surrounding environment and converts it into electrical energy. The focus of this research is to design and implement an energy harvester powered by Radio Frequency (RF), specifically in the 2.4 GHz frequency band for ultra-low power IoT sensor applications. The RF energy harvester (RFEH) was designed and simulated using ADS 2011.11 software. The RFEH was fabricated on FR4 epoxy PCB and the measurement was conducted in two conditions: directly connected to the signal generator and in a far-field area. The harvester achieved a maximum output current of 32.6µA under a received power of -3 dBm, satisfying the requirements for ultra-low power IoT sensors.